Molecular diagnostic methods for identifying Serrasalmid fish (Pacu, Pirapitinga, and Tambaqui) and their hybrids in the Brazilian aquaculture industry - Hashimoto, Diogo Teruo [UNESP]; Mendonca, Fernando Fernandes [UNESP]; Senhorini, Jose Augusto; Oliveira, Claudio de [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Elsevier B.V., 2011)
Hybrids of fish obtained by crossing commercial species of the family Serrasalmidae (Pacu, Pirapitinga, and Tambaqui) have been produced on a large scale by the Brazilian aquaculture industry. However, because juvenile stages are morphologically indistinguishable, pure species and hybrid stocks may be easily mixed in breeding facilities, which may ultimately reduce production on farms and could have adverse impacts on native populations, through escape of fertile hybrids to the wild. We established molecular markers using mitochondrial and nuclear genes to identify hybrid lineages of Serrasalmids and characterize them in relation to their parental species, Colossoma macropomum, Piaractus mesopotamicus, and Piaractus brachypomus. Using these diagnostic molecular tools, we then examined fish purchased from two seed producers and detected substantial admixture of pure stocks and their various hybrids. Further application of these diagnostic genetic tools is needed to assess the impacts of hybridization and stock admixture, both in the aquaculture industry and in the environment. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Molecular identification; Conservation genetics; Hybridization; Molecular markers